VATS-lymph node dissection, staging and restaging in advanced malignancy/the Munich experience - Hiebinger, Andreas; Öfner-Velano, Dietmar; Bodner, Johannes (Video-Assisted Thoracic Surgery, 2018)
In NSCLC an accurate staging of the mediastinum and in particular its lymph nodes is mandatory to determine accurate therapy, prevent futile surgery and identify those patients who eventually will benefit from a multimodality treatment setting including pre-surgical induction therapy. This review provides an overview on current standards of mediastinal staging in NSCLC followed by the presentation of the authors’ institutional practice. While the introduction of integrated positron tomography and computed tomography (PET/CT) has significantly improved non invasive clinical staging, the invasive mediastinal staging was revolutionized by ultrasound-based endoscopic fine needle aspiration with an accuracy surpassing that of the pervious gold standard—cervical mediastinoscopy. After many decades, the dogma of a “clear or cleared off” mediastinum as a prerequisite for primary tumor resection in curative intention has been re-evaluated and consequently has fallen: if PET positive mediastinal nodes are considered resectable, patients are referred to initial surgery without further invasive staging or induction therapy in many centers; in those patients with unresectable N2 disease however, histological proof is still of high importance but invasiveness is kept as minimally as possible, starting with endoscopic techniques and only eventually accelerating to surgical ones like VAM and VATS. In contrast to any other staging tool, VATS allows for a combination or cascade of diagnostic (re-)staging and therapeutic resection within a single procedure: the initial evaluation of histology and respectability of the mediastinal lymph nodes during a diagnostic systematic or selective mediastinal dissection is eventually followed by the anatomical tumor resection.